The Influence of Transformational Leadership, Talent Management and Job Placement on Employee Performance in the Personnel Division of the Directorate General of Food Crops, Ministry of Agriculture in Jakarta - Yantina Aprila; Ahmad Cik; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the influence of Transformational Leadership, Talent Management and Work Placements on Employee Performance in the Personnel Division of the Directorate General of Food Crops, Ministry of Agriculture in Jakarta. This type of research uses descriptive quantitative methods and inferential analysis using primary data in the form of a closed questionnaire to 100 respondents and multiple linear regression analysis data to test the research hypothesis. The results showed that Transformational Leadership, Talent Management and Job Placement simultaneously had a positive and significant effect effect on employee performance. In an effort to improve employee performance, the Personnel of the Directorate General of Food Crops, Ministry of Agriculture in Jakarta needs to pay attention and know what the problem is because it can be used as a basis for evaluating weaknesses and maintaining employee effectiveness through Transformational Leadership, Talent Management and Good Work Placements.